Pendekatan Ekologi dalam Studi Islam sebagai Landasan Etika Pelestarian Lingkungan - Muhammad Soleh Aminullah (Medan Resource Center, 2025)
This study aims to examine the concept of ecology within Islamic studies, explore the ecological approaches employed to understand the relationship between humans and the environment, and analyze the practical implementation of these approaches in environmental management and conservation from an Islamic perspective. The research adopts a qualitative design using a library research approach. Data were collected through a comprehensive review of the Qur'an, Hadith, scholarly books, peer-reviewed journal articles, and other relevant literature addressing ecology, environmental ethics, and Islamic thought. The data were analyzed using a descriptive-analytical method by integrating normative and conceptual approaches to interpret the ecological values embedded in Islamic teachings. The findings reveal that ecology in Islam extends beyond the reciprocal relationship between living beings and their environment, encompassing humanity's spiritual responsibility as khalifah (steward) of the Earth. The Islamic ecological framework is founded upon the principles of tawhid, amanah, rahmatan lil-'alamin, ta'abbud, ta'aqquli, and takhalluq, which collectively shape a comprehensive environmental ethic. The study further demonstrates that the practical application of these principles promotes sustainable natural resource management, prevents excessive environmental exploitation, strengthens ecological awareness, and affirms that environmental conservation constitutes an integral expression of Islamic teachings as well as a fundamental moral obligation of humankind.